Cost-Effectiveness of Asthma Step-Up Therapy as an Increased Dose of Extrafine-Particle Inhaled Corticosteroid or Add-On Long-Acting Beta2-Agonist. Issue 1 (June 2016) - Roche, Nicolas; Colice, Gene; Israel, Elliot; Martin, Richard; Dorinsky, Paul; Postma, Dirkje; Guilbert, Theresa; Grigg, Jonathan; Aalderen, Willem; Barion, Francesca; Hillyer, Elizabeth; Thomas, Victoria; et al.
Abstract Introduction Data from different healthcare systems on relative cost-effectiveness of asthma step-up therapy strategies are required to inform decision-makers and clinicians. Our objective was to compare cost-effectiveness from the United Kingdom National Health Service perspective of three step-up strategies for patients with asthma uncontrolled by inhaled corticosteroid (ICS) monotherapy. Methods This was a historical matched cohort cost-effectiveness analysis of anonymized medical records for patients with asthma of age 12–80 years. We conducted two-way comparisons of step-up therapy using increased dose (≥50%) of extrafine-particle ICS or add-on long-acting β2 -agonist (LABA) via fixed-dose combination (FDC) ICS/LABA inhaler or via separate inhaler. The incremental cost-effectiveness ratio (ICER) was calculated using asthma-related direct costs during one outcome year and a composite measure of risk-domain asthma control (no asthma-related hospital attendance, acute oral corticosteroids, or consultation for lower respiratory tract infection). Results Patients prescribed ICS dose step-up (n  = 3036) had significantly lower baseline-adjusted, mean asthma-related healthcare costs during the outcome year than those prescribed FDC ICS/LABA (n  = 3036; mean difference, £124/year). ICS dose step-up had 56% probability of being less costly and marginally less effective (a trade-off), with ICER of £51, 449 per additional patient controlled with FDC; and ICS dose step-up had 44% probability of being the preferred treatment strategy (less costly and more effective). In a second comparison, ICS step-up (n  = 3232) had 100% probability of being cheaper and more effective than adding LABA to ICS via separate inhalers (n  = 6464). Conclusion For asthma step-up therapy, increasing ICS dose using extrafine-particle ICS is significantly less costly from the payer perspective and marginally (non-significantly) less effective than FDC ICS/LABA therapy containing standard fine-particle ICS. These findings apply primarily to the UK healthcare system but warrant consideration when developing guidelines in settings with strong economic constraints. Trial Registration ClinicalTrials.gov identifier: NCT01697722. Funding Teva Pharmaceuticals Limited, Petach Tikva, Israel.